Population Status, Menaces and Management of Rhesus macaque (Macaca mulatta) and Tarai gray langur (Semnopithecus hector) in the Forest of Dharan and its Vicinities - Tamang, Ganesh; Thapa, Ganesh Bahadur; Kharel, Milan; Subba, Asmit; Pradhan, Ashish (Himalayan Journal of Science and Technology, 2020)
The present study was conducted in 28 spots of 10 sampling sites including forest and urban areas of northern part of Dharan, Sunsari District (26.7944° N, 87.2817° E, 349 m msl) and its vicinities in the Province No. 1 of Nepal. The scan sampling method was applied to count the monkey population and their menace was surveyed through the questionnaires and direct field observations. In present study, 69.31% (n=558) Rhesus monkeys species and 30.68% (n=247) Tarai gray langurs were counted within 192.6 km2 of the study site. In 14 troops of Rhesus monkeys and 9 troops of Tarai gray langurs, the gender dominance of female Rhesus monkey and female Tarai grey langur were found to be 40.32% and 58.74% respectively. Whereas, the average male-female ratio was found to be 1:8.3 and 1:5.1 for Rhesus monkey and Tarai gray Langur respectively. The largest single troop recorded was of Rhesus monkey (n=125). A total of 25.2 quintals crops was damaged by both monkeys from the study area this year. Maize (42%) was found to be major crop damaged by Rhesus monkeys. Management of non-human primates through further research is urgently required to minimize their menace and to protect people from the risk of transmission of possible zoonotic diseases. The result of this study can be implied practically for the management of monkey’s menaces not only to the Dharan but also to other monkey affected areas of the country.